The Relationship Between Motor Competence and Physical Fitness from Early Childhood to Early Adulthood: A Meta-Analysis - Utesch, Till; Bardid, Farid; Büsch, Dirk; Strauss, Bernd (Sports medicine (Auckland), 2019)
Background Motor competence and physical fitness are important factors for promoting positive trajectories of health over time. In 2008, Stodden and colleagues developed a model that discussed the role of both factors in physical activity. Furthermore, the authors hypothesized that the relationship between motor competence and physical fitness is reciprocal and changes over time. Objective The aim of the present meta-analysis was to synthesize the evidence on the relationship between motor competence and components of physical fitness from early childhood to early adulthood and the potential influence of age. Methods Scientific databases Web of Science and PubMed were used for the literature search. German- as well as English-language studies were included that assessed typically developing children. In accordance with the PRISMA guidelines, 93 studies between 2005 and June 2018 were screened in full. Nineteen studies comprising of 32 samples, 87 single data points from 15,984 participants aged 4.5–20.4 years ( M age = 11.44, SD = 4.77) were included in the analysis. Results A random effects model was conducted for the meta-regression with age as moderator variable. The relationship between motor competence and physical fitness was moderate to large ( r = 0.43, p < 0.001) after controlling for multiple effects, including dependent samples and small sample sizes in the quantitative synthesis. Additionally, age was a small significant positive moderator of the effect size. Conclusions and Implications The findings provide support for a moderate to large positive relationship between motor competence and physical fitness that strengthens with increasing age. However, the results also indicate that there may be an overlap in content between motor competence and physical fitness assessments, which warrants further investigation. More research is also needed to assess similarities and differences in terms of the construct structures.